Analyzing Legal Frameworks in Emergency Care: Insights for Midwifery Education - A Scoping Review - Ni Made Ayu Saskarani; Sagung Putri ME Purwani; Ni Ketut Supasti Dharmawan; Supriatin Supriatin; Sari Hastuti (Postgraduate, University of Mataram, 2023)
Emergency situations in midwifery care during pregnancy, labor, and the postnatal period can arise unexpectedly. It is crucial for midwives to be knowledgeable about the legal frameworks governing the protection provided to them in the execution of their professional responsibilities. This scoping review aims to explore the legal protection provided to midwives in emergency situations through a search of relevant literature in bibliography databases and hand-searching, and employed the Participant, Concept, and Context (PCC) principle to formulate the eligibility criteria. Data extraction was conducted using the PRISMA flow diagram. The analysis was conducted using a meta-aggregation approach to map the legal framework for emergency midwifery care from available studies. The review found key themes that emerged from the review included legal protection and scope of practice, midwives' authority in emergency care, importance of competencies and certifications, challenges and power imbalances in midwifery practice, and midwives' dissatisfaction and professional deviation. Â This scoping review underscores the importance of legal protection and scope of practice for midwives